Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3389/fmicb.2022.875234
|View full text |Cite
|
Sign up to set email alerts
|

Hurricane Harvey Impacts on Water Quality and Microbial Communities in Houston, TX Waterbodies

Abstract: Extreme weather events can temporarily alter the structure of coastal systems and generate floodwaters that are contaminated with fecal indicator bacteria (FIB); however, every coastal system is unique, so identification of trends and commonalities in these episodic events is challenging. To improve our understanding of the resilience of coastal systems to the disturbance of extreme weather events, we monitored water quality, FIB at three stations within Clear Lake, an estuary between Houston and Galveston, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
0
1
0
Order By: Relevance
“…previous study where it was observed that the fecal indicator bacteria level decreased a few weeks after the flood event when the dewatering process was done [5,27]. In NC samples, E. coli concentration were observed higher in the flooded sites (F2, F3, F4, F6, and F8) than in unflooded locations.…”
Section: Plos Onementioning
confidence: 68%
“…previous study where it was observed that the fecal indicator bacteria level decreased a few weeks after the flood event when the dewatering process was done [5,27]. In NC samples, E. coli concentration were observed higher in the flooded sites (F2, F3, F4, F6, and F8) than in unflooded locations.…”
Section: Plos Onementioning
confidence: 68%